Study of the cervical canal microbiome and microbiocenosis in reproductive-age women with squamous intraepithelial lesion - Peremykina, Anastasiya; Cheranev, Valery; Shilyaev, Alexey Y.; Krivoy, Andrey; Repinskaia, Zhanna; Korostin, Dmitriy; Rebrikov, Denis (Frontiers in Microbiology, 2025)
IntroductionThe study of the cervicovaginal microbiome is a critical area of research in medical science. According to scientific data, microorganisms inhabiting the lower female genital tract may influence susceptibility to and persistence of human papillomavirus (HPV), as well as the development and progression of squamous intraepithelial lesions (SIL) toward cervical cancer (CC).MethodsThe study included 67 patients with a histological diagnosis of low-grade squamous intraepithelial lesion (LSIL) and 85 patients with high-grade squamous intraepithelial lesion (HSIL). The cervical canal microbiome of patients with LSIL (n = 31) and HSIL (n = 45) was examined using the 16S rRNA gene sequencing method, while the microbiocenosis of the remaining patients with LSIL (n = 36) and HSIL (n = 40) was analyzed using PCR-RT.ResultsThere are patients with HSIL on average older than patients with LSIL about 3 years. HPV 16 was found to be the most common virus type in patients with SIL. When determining of 16S rRNA genes of prokaryotic microorganisms in women of reproductive age with SIL by the new generation sequencing, it turned out that the cervical canal microbiome is inhabited by many atypical representatives (soil, aquatic and aerobacteria). In addition to the genera Lactobacillus, Streptococcus, Staphylococcus, Gardnerella, Ureaplasma, Prevotella, Sneathia, Fusobacterium, Veillonella, Megasphaera, Dialister, Enterococcus, Escherichia/Shigella, Fannyhessea, Peptococcus, Peptostreptococcus, Finegoldia, Porphyromonas, Corynebacterium, Alloscardovia, Mageeibacillus, Haemophilus, Duncaniella, Ralstonia, Sphingomonas, Pedobacter, Methylobacterium, Ruminococcus, Sediminibacterium, Pseudomonas, Aerococcus, Acinetobacter, Campylobacter, Stenotrophomonas, Sphingobacterium, Phyllobacterium and others may be included in the microbial composition of the cervical canal. Dysbiotic disorders were more common in patients with HSIL. Streptococcus spp. always accompanied aerobic vaginitis (AV), whereas bacterial vaginosis (BV) was associated with the genera Gardnerella, Fannyhessea, Prevotella, Dialister, Sneathia, Anaerococcus, Megasphaera, Finegoldia, Peptoniphilus, Porphyromonas, Parvimonas and Eubacterium spp. When comparing the two methods, the genera Peptoniphilus, Methylobacterium, Ralstonia spp, Sphingomonas, Phyllobacterium, Parvimonas, Anaerococcus and Ruminococcus may be included in the microbial biomass in a significant proportion. Eubacterium spp. did not occur in the 16S sequencing method. Some representatives are detected together with each other in the RT-qPCR method (Femoflor - 16), e.g., Sneathia spp. + Leptotrichia spp. + Fusobacterium spp.; Megasphaera spp. + Veillonella spp. + Dialister spp.; Mobiluncus spp. + Corynebacterium spp., however, Corynebacterium spp., Veillonella spp., Mobiluncus spp., Fusobacterium spp., Leptotrichia spp. and Peptostreptococcus spp. were practically absent (or in a low percentage) in the microbiome of women with SIL.